Legal Protection for Online Transportation Drivers: An Approach to Gender Inclusiveness in Indonesia - Musyaffa, Nadhif Fadhlan; Iswari, Rani Dian (Sawwa: Jurnal Studi Gender, 2024)
In line with the employment numbers the online transportation industries have created, many problems are still related to its workers. Legal protection is needed to regulate this industry for promoting gender inclusiveness. By using the sociology of law concept and gender theory, the objective of this research is to have a comprehensive understanding of the reason for the urgency of legal protection in the scope of the online transportation industry and how it can be correlated with promoting gender-inclusiveness implementation. This article used the juridical-empirical research method. This research used a statutory approach using primary data from interviews, ministries, and departments in Indonesia and secondary data from scientific journals and books. The research found that legal protection can be the social engineering for changing societies’ mindsets and behavior toward the drivers of the online transportation industry. Also, the law is considered social control by policy-makers to implement gender-inclusiveness in Indonesia. This study shows that legal regulations designed as social engineering and social control can transform the gig economy ecosystem into a safer, fairer, and gender-inclusive workspace for female drivers.